LTCC-technology for Producing Hexaferrites - D.N. Chitanov; V.G. Kostishyn; L.V. Kozhitov; P.A. Ryapolov; A.Yu. Adamtsov (Журнал нано- та електронної фізики)
In the review examined the possibility of using LTCC-technology for obtaining hexaferrites as reaction additives glasses Bi2O3-B2O3-SiO2-ZnO (BBSZ) and BaCu (B2O5) (BCB) to reduce the sintering temperature. It is shown that compatibility between hexaferrites with the addition BBSZ, BCB and silver paste, which is a key requirement in the manufacturing process LTCC-components. Considered the possibility of co-sintering of ferrites and dielectric tape composites. It was established that for the realization of defect-free LTCC-composite need to control the shrinkage of the two tapes. In this connection becomes an important concept of zero shrinkage and limiting sintering.